2019
DOI: 10.1002/14651858.cd013393
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-blockers after shock wave lithotripsy for renal or ureteral stones in adults

Abstract: Analysis 2.1. Comparison 2: Alpha-blocker and usual care versus usual care: stone location subgroup (renal and proximal ureter versus distal ureter), Outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The rationale underlying the use of alpha-blockers as MET is based on the presence of alpha-adrenoceptors in the ureter, which mediate contractility [30]. Contractility of the ureters in the presence of a stone may prevent passage [6]. Therefore, blocking alpha-adrenoceptors with alpha-blockers results in a reduction in contractility, thus dilating the ureter, theoretically increasing the likelihood of stone passage [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The rationale underlying the use of alpha-blockers as MET is based on the presence of alpha-adrenoceptors in the ureter, which mediate contractility [30]. Contractility of the ureters in the presence of a stone may prevent passage [6]. Therefore, blocking alpha-adrenoceptors with alpha-blockers results in a reduction in contractility, thus dilating the ureter, theoretically increasing the likelihood of stone passage [6].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous studies [6], we examined the likelihood of individual postoperative complications and categorized these according to the Clavien-Dindo system, as well as identifying the number of patients needing auxiliary procedures following MET after ESWL. We have shown that MET following SWL reduces the risk of the postoperative complications of pain and steinstrasse compared to control, and thus significantly decreases the need for auxilliary procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in the vascular system, α 1 -AR antagonists affect the contraction of smooth muscle in several organ systems. α 1 -AR blockage results in the relaxation of smooth muscle in the prostate and ureter to increase urinary flow [ 98 , 99 , 100 ]. Since the 1980s and 1990s, α 1 -AR antagonists are frequently used medications in the management of benign prostatic hyperplasia (BPH), kidney stones, and in therapy-resistant arterial hypertension, two conditions frequently found in older adults.…”
Section: α 1 -Ar Antagonistsmentioning
confidence: 99%